LEGAL CONSEQUENCES OF AGREEMENT IN ISLAMIC ECONOMIC BUSINESS - Trubus Wahyudi (Jurnal Pembaharuan Hukum, 2020)
The purpose of this article is to find out The Essence of Akad in Islamic Economic Business and the legal consequences in applying the sanctions for sharia economic disputes against parties who are in default. The approach method uses normative juridical, the results of research found include economic business engagement must be oriented to the principles of justice, partnership and transparency and does not contain gharar (fraud), maysir (gambling), usury, zhulum (persecution), riswah (bribery), haram and immoral goods, The legal consequences of applying sanctions in cases of sharia economic disputes against parties who default must be considered in the application of sanctions appropriately, whether the application of sanctions is cumulative or alternative sanctions from various kinds of sanctions in the form of paying compensation, cancellation contract, transfer of risk, fines, pay court fees.